Bismuth‐Mediated Diastereoselective Allylation Reaction of Carbonyl Compounds with Cyclic Allylic Halides or Cinnamyl Halide. Issue 3 (11th December 2018) - Liu, Xuan‐Yu; Cheng, Bu‐Qing; Guo, Yi‐Cong; Chu, Xue‐Qiang; Li, Yong‐Xin; Loh, Teck‐Peng; Shen, Zhi‐Liang
Abstract: An efficient diastereoselective allylation of various carbonyl compounds with cyclic allylic halides by using commercially available bismuth powder in the presence of LiI was developed. Among all the metals screened, bismuth was found to be the best mediator for the transformation. The reactions involving various cyclic allylic halides proceeded smoothly at room temperature to produce the desired homoallylic alcohols in good to excellent yields with high diastereoselectivities (>99:1 dr). Reversed diastereoselectivity was obtained when carbonyl substrate (e. g., 2‐pyridinecarboxaldehyde, glyoxylic acid) containing chelating substituent was used in the allylation reaction. In addition, the reactions involving acyclic ( E )‐cinnamyl bromide as substrate worked equally well with high diastereocontrol. Abstract :